Central Bank Independence and Inflation: The Matters of Financial Development and Institutional Quality - Agung Kunaedi; Darwanto Darwanto (Signifikan: Jurnal Ilmu Ekonomi, 2020)
The inverse relationship between the independence of the central bank (CBI) and inflation became a consensus that trusted throughout the world. However, there is no conclusive explanation of why and how central bank independence has succeeded in suppressing inflation. The purpose of this study is to examine the influence of financial development and institutional quality on the relationship between central bank independence and inflation. Using 20 Countries of Asia with institutional diversity, this study analyzed through a dynamic panel approach (GMM-Arellano and Bond Estimator). The result indicates that the inverse relationship between central bank independence and inflation depends on the development of the financial sector and also the institutional quality of each country. In other words, to make the central bank's independence work effectively in order to solve bias inflation, the improvement of the financial sector and also the institutional quality is needed.JEL Classification : E580, E310, E020 How to Cite:Kunaedi, A., & Darwanto. (2020). Central Bank Independence and Inflation: The Matters of Financial Development and Institutional Quality. Signifikan: Jurnal Ilmu Ekonomi, Vol. 9(1), 1-14. doi: http://dx.doi.org/10.15408/sjie.v9i1.12899.